Endomysial antibody: is it the best screening test for coeliac disease?. Issue 12 (December 1992) - Ferreira, M; Davies, S L; Butler, M; Scott, D; Clark, M; Kumar, P
Abstract : The sensitivities and specificities of the IgA and IgG antigliadin antibody and the IgA antireticulin antibody have been compared with the recently described endomysial antibody directed against the basement membrane of smooth muscle in monkey oesophagus. One hundred and seventeen patients with adult coeliac disease (21 untreated), 84 patients with inflammatory bowel disease, systemic lupus erythematosus and rheumatoid arthritis (comprising the disease control group), 47 normal controls and a miscellaneous group of 29 patients, who were selected because of a positive reticulin staining pattern, were investigated. These results were correlated with the degree of abnormality of the intestinal mucosa in patients with adult coeliac disease. Endomysial antibodies were found in all patients with untreated coeliac disease and subtotal villous atrophy and in 47% of patients on a non-strict gluten free diet. One patient on a strict gluten free diet was positive and had partial villous atrophy while all patients in disease control groups were negative. Results were variable with the antireticulin and antigliadin antibodies. Sensitivity and correlation with subtotal villous atrophy in the untreated patients was 100%. It is concluded that the endomysial antibody is superior to other current antibody tests and should be used in preference for the diagnosis of coeliac disease.